KERJA SAMA CAPACITY BUILDING ANTARA BADAN NARKOTIKA NASIONAL REPUBLIK INDONESIA - AUSTRALIAN FEDERAL POLICEPERIODE 2015 - 2019 - Ahmad Arfan, - (2022)
Narcotics is a crime that has existed since ancient times until now. Narcotics know no age, all age groups can be affected. So that in this era of globalization, it is easy for someone to become a target for smuggling or this drug. In 2011, the National Narcotics Agency of the Republic of Indonesia (BNN RI) and the Australian Federal Police (AFP) collaborated in the context of eradicating illicit narcotics smuggling. These efforts are made to fight crime crimes. With the growing motives and crimes of crime, there needs to be an innovation in capacity building carried out by the Australian Federal Police (AFP) against the National Narcotics Agency of the Republic of Indonesia (BNN RI). This study aims to describe the process and implementation of what has been done in the collaboration between the National Narcotics Agency of the Republic of Indonesia (BNN RI) and the Australian Federal Police (AFP). The researcher uses the classical Liberalism approach with the Interdependence method in looking at the cooperation between the two agencies. Researchers also use the concept of narcotics as a transnational crime, as the main topic and also to see the level of danger from narcotics. The researcher uses the concept of capacity building, which is to see the dimensions of the cooperation carried out by the two agencies. And researchers also use the MoU concept in knowing and a tool to review the MoU in collaboration with the National Narcotics Agency of the Republic of Indonesia (BNN RI) and the Australian Federal Police (AFP). The use of qualitative research methods with a descriptive approach was chosen by the researchers to be able to describe the process of cooperation and implementation of capacity building cooperation within the framework of the cooperation between the National Narcotics Agency of the Republic of Indonesia (BNN RI) and the Australian Federal Police (AFP). The results of this study indicate the implementation of capacity building in the field of canine (K-9), intelligence, and personnel development in the field of language and leadership.